2019
DOI: 10.1186/s12893-019-0628-z
|View full text |Cite
|
Sign up to set email alerts
|

Long term outcomes from lymphatic venous anastomosis after total hysterectomy to prevent postoperative lymphedema in lower limb

Abstract: BackgroundLymphedema in lower limb is one of major postoperative complications followed by a total hysterectomy with lymph node dissection. The objective of this report is to examine a long-term result of lymphaticovenous anastomosis procedure as a preventive surgery.MethodsSixteen patients with endometrial cancer underwent an abdominal hysterectomy with a bilateral salpingo-oophorectomy. Just after pelvic lymph node dissection, either end-to-end or sleeve anastomosis utilizing venules and suprainguinal lymph … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…However, because these factors caused mild and temporary damage of the skin barrier, they did not seem to be the risk factors for erysipelas relapse [ 10 ]. Surgery can change the local tissue structure and cause poor lymphatic reflux [ p < 0.0001, OR 4.1 (95% CI 2.4–7.1)] [ 11 ]. The results of univariate analysis further indicated that surgery was not the only risk factor for erysipelas, but there were other risk factors as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, because these factors caused mild and temporary damage of the skin barrier, they did not seem to be the risk factors for erysipelas relapse [ 10 ]. Surgery can change the local tissue structure and cause poor lymphatic reflux [ p < 0.0001, OR 4.1 (95% CI 2.4–7.1)] [ 11 ]. The results of univariate analysis further indicated that surgery was not the only risk factor for erysipelas, but there were other risk factors as well.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). 5 14 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 An overview of each study is summarized in Supplementary Table S2 (available online only). Ten and six single-arm studies reporting outcomes of PLS for upper ( Supplementary Table S3 ; available online only) and lower ( Supplementary Table S4 ; available online only) extremity CRL were included, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…ILR is commonly performed for BCRL primary prevention, which is known as Lymphatic Microsurgical Preventive Healing Approach (LYMPHA) (boccardo 1,2,3,4). Several studies have also applied ILR for primary lymphedema prevention in the lower extremity (Ezawa et al, 2019; Wagner et al, 2022; Wan et al, 2022). However, the surgical concept can also be served for secondary prevention.…”
Section: Discussionmentioning
confidence: 99%